The evolution of regional trials and collaboration in Central America, 1955 to 1988 - Dessert, J.M. (Southern Africa Development Coordination Conference (SADCC), 1989)
The paper describes the development of collaborative research on beans in Central America, Mexico, Colombia and Venezuela, since the 1950s. National bean research programs were established in all countries by the 1960s. The PPCMCA was formed in 1955 and extended to beans (PPCMF) in 1962, when the first regional trial was composed. IICA assumed responsibility for the management of regional trials in 1965, now numbering three for different seed types and purposes. In 1969, it was proposed that regional collaboration be extended to other disciplines but, for various reasons, this was not accomplished. Similarly, the regional trials system was abandoned. Bean research began at CIAT in 1971 and, following a workshop in 1975, the first IBYAN was formulated, replacing the former regional trials of the PCCMF. Collaboration was further strengthened by the development of the CIAT regional programme in Central America. In 1977, the VEF and the EP trial series and various international disease nurseries were initiated and, with the IBYANs, remained the chief sources of new materials until the early 80s, when truly regional trials again emerged. The present structure of the system is described. (AS)